Efeito do hcg na produção de sêmen do curimbatá (Prochiodus scrofa Steindachner, 1881) - KAVAMOTO, EMICO TAHIRA; NARAHARA, MASSUKA YAMANE; MAINARDES-PINTO, CLEIDE S. R.; ANDRADE-TALMELLI, ELAINE FENDER DE; ROMAGOSA, ELIZABETH; FERRAZ, EDUARDO DE MEDEIROS (Revista Ceres, 2015)
.